Massive atmospheric sulfur loading of the AD 1600 Huaynaputina eruption and implications for petrologic sulfur estimates - Costa, Fidel (2012)
We combine petrological, analytical, and thermodynamical data to constrain the sulfur yield of the AD 1600 Huaynaputina eruption which has been associated with the largest Earth's temperature shift in the last 600 years. The calculated amount of S (26-55 Tg), partly overlaps, but ranges to almost twice the amount estimated from ice-core data (16-32 Tg), the higher values of our estimate probably reflect that not all S released by the eruption reached the stratosphere. Our study also shows that it is possible to estimate the atmospheric sulfur loading from the volcanic products themselves, which opens the possibility to explore volcano-climate links beyond the time period covered by ice-core archives.